Total factor productivity growth in China's corn farming: An application of generalized productivity indicator - Zhiyong Niu; Yining Zhang; Tianxiang Li; Tomas Baležentis; Dalia Štreimikienė; Zhiyang Shen (Journal of Business Economics and Management (JBEM), 2021)
Total factor productivity (TFP) growth measures usually focus on a certain direction of optimization and ignore the general setting encompassing the input and output orientations simultaneously. This paper uses the generalized Luenberger-Hicks-Moorsteen (LHM) TFP indicator which is additively complete and can be decomposed by three mutually exclusive elements. The input- and output-oriented analysis is undertaken in order to derive the generalized TFP measured. The paper uses the corn production data from 19 Chinese provinces over the period of 2004-2017. This research is important as China is the second largest corn producer in the world. The TFP growth was observed for Chinese corn farming the rate of 0.56% per year. The technological progress (0.48%) was the major source of the TFP growth, whereas the importance of the technical efficiency change (0.09%) and scale efficiency change (-0.01%) was negligible.
Keywords: M41; C83; L20; 650; corn production; total factor productivity; Luenberger-Hicks-Moorsteen indicator; data envelopment analysis; efficiency change; technological progress